Atravessamentos subjetivos na posição sujeito-professor em um instituto de idiomas - Walmiro, Mariá Prado (2019)
This thesis aims at discussing the effects of the ideological interpellation of a language institute methodological discourse over a teacher and to problematize, in what extent, the subjectivity concerns the interpellation ritual by setting some resistance evidences related to the teacher’s subjectivity in her subject-teacher position of an English teacher. My proposal, therefore, is to analyze the sayings of an English teacher, in order to discuss the points of resistance in the classroom ritual, in which the “method” discourse heckles a teacher. The great question that motivated me to perform this research is to understand how the teacher’s subjectivity can represent loopholes in this injunction of the methodological discourse in a language institute and, consequently, in the classroom ritual. Motivated by this question, I assume that what constitutes a teacher subjectively echo stronger than any injunction of an institute and a methodological discourse are able to wield on the subject. My hypothesis is, despite the “method” interpellation strength over the teacher, her representations of language, language teaching-learning and oral-enunciative competence is related to the way she puts herself in the subject-teacher position and, as a consequence, shows disruptions in this interpellation that the “method” discourse wield on her as a subject-teacher. The object of analysis of this thesis is the participant teacher’s transcription saying in articulation with the theoretical which I am based on. The specific objectives of this study are: a) raising and analyzing the representations of language, language teaching-learning and oral-enunciative competence in the teacher’s saying relating or contrasting them to the theoretical basis that the institute “method” consists; and b) problematizing the crossing of the teacher’s subjective constitution in the interpellation that she undergoes as subject-teacher of a certain methodology. In order to develop this research, I have proposed a case study aimed at discussing the questions that involve this thesis. The research instruments were: a) an informative questionnaire to understand a little more about the teacher’s profile and also his trajectory with the English language teaching-learning process; and b) transcription of oral interviews that followed a semi-structured model of questions, which provides a speech instance for the research participant about her discourse inscription in the institute methodological discourse, her relation with the foreign language, her representation (s) of language, language teaching-learning and oral-enunciative competence. The analysis show that the subjectivity is able to cross the methodological discourse injunctive strength which the teacher suffers interpellation points to confirm the hypothesis of this research.